APPROACH TO CHEMICAL LEARNING IN CONTROL OF EXHAUST GAS EMISSIONS IN AUTOMOTIVE SKILLS - giri sena gautama (Edusentris, 2021)
Environmental quality is one of the important issues in achieving the results of national development. One of the results of development is an increase in economic capacity marked by an increase in income per capita. This will be directly proportional to the increase in ownership of tertiary consumption goods, one of which includes vehicles.The quality of vehicle engines using fossil fuels (fossil combustion engines) does not always produce a number of environmentally friendly exhaust gas particles, one of which is caused by vehicle operational factors. Control of vehicle exhaust emissions is done through maintenance procedures of vehicle engines in the workshop (workshop) designated. In the vehicle maintenance procedure, there is a standard indicator of the amount of exhaust emissions which must be understood in accordance with certain vehicle specifications. The size and number of particles of the product of chemical reactions combustion air and fuel are analyzed.Human resources who are responsible technically and operationally in vehicle maintenance are mechanics (automobile technician). Vocational High Schools (Sekolah Menengah Kejuruan/SMK) in Light Vehicle Engineering Skills Competencies as institutions that produce graduates as mid-level vehicle technicians, must be equipped with basic concepts of science in supporting the implementation of skills competency learning. Chemistry learning is one of the subjects directly related to the analysis of the results of combustion chemical reactions, in the subject matter of the procedure for testing exhaust emissions.Chemistry learning approach can help students in concluding the results of the analysis of parameters released from vehicle exhaust gases, through an emission test tool (Gas Analyzer). The results of the analysis lead to the exhaust emission test procedure, one of which is the CO concentration adjustment. There is a difference between students who understand the chemical equation of combustion reaction and those who do not understand the chemical equation of combustion reaction, the procedure of adjusting CO concentration and analysis of the causes of differences or problems with the standard CO concentration values.Chemistry learning approach in the process of learning periodic maintenance procedures, in this case the exhaust emissions test is carried out in theory and practicum classes in vehicle repair shops. The learning process in Classroom Action Research (CAR) applies the Problem Based Learning (PBL) learning model. The PBL model was chosen because: a) Students obtain basic knowledge (sciences) that is useful for solving engineering problems, b) Students learn actively and independently with a presentation of material that is integrated and relevant to actual reality, and c) Students are able think critically, and develop initiatives especially the ability to solve problems according to the way students think.This Classroom Action Research (CAR) applies the John Elliot model with 2 (two) cycles. Each cycle has four stages namely planning, implementing, observing and reflecting. If the goal has not been reached, then the next cycle is carried out with the same stages. Data on the results of research with PBL learning models were obtained from observations of the PBL learning process observation, tests to assess student learning outcomes, and interviews with students.PBL learning model in CAR can improve students' learning completeness, including the stages of problem solving. But there are exceptions in the checking stage of problem solving.